Project management: Lean vs. Agile methodology - Georgakalou, Maria; Koutsikos, Kostas (International Conference on Business and Economics - Hellenic Open University, 2023)
The past decades there has been a large discussion on the suitability of the lean and the agile methodologies for an effective project management. This paper aims at providing an answer to this question. Both theoretical facts and practical case studies are going to be examined in order to be able to reach a result. It seems that both methodologies might be good, depending on the problem under consideration. The two methodologies have some differences both on their starting point (LEAN was initially used in the manufacturing sector, while AGILE was initially used by the software development sector) and on their general concept (LEAN being more holistic and long-term, while AGILE is a better tool when quick decisions are needed). Aspects such as reliability of the methodologies and their challenges including reasons that might lead to failure are going to be discussed. EL Classifications: M10 General, M11 Production Management, M19 Other Keywords: LEAN methodology, AGILE methodology, Project management, effectiveness, efficiency